Analisis Strategi Pemasaran Digital Dalam Meningkatkan Penjualan Produk Indihome PT Telekomunikasi Selular Branch Karawang-Purwakarta - Yulianingsih, Silvi; Mulyadi, Dedi; S, Sungkono (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to analyze the digital marketing strategy implemented by PT Telekomunikasi Selular, especially in the Karawang - Purwakarta branch, in an effort to increase sales of IndiHome products. In the current digital era, marketing through digital media is one of the key factors in achieving higher sales targets. This research uses a qualitative descriptive approach with a case study method to get an in-depth picture of the implementation of digital marketing strategies. Data was collected through in-depth interviews with the marketing team and document analysis related to the marketing strategies used. The research results show that the use of social media and paid advertising campaigns are the main strategies used. The effectiveness of these strategies is demonstrated by the significant increase in the number of customers and sales of IndiHome products in the research period. The conclusions of this research indicate that the right digital marketing strategy can significantly increase product sales.